Representasi Politik Perempuan dalam Pilkada Serentak 2015 fi Indonesia - Sholikin, Ahmad (Jurnal Review Politik, 2016)
This paper examines the political representation of women in Simultaneous Regional Elections which was held in 2015. The research focuses on how the representation of women in executive nomination (Regent/Mayor and Deputy Regent/Deputy Mayor) in Simultaneous Regional Elections 2015. Question derivative of this study is about how the journey of political representation of women and how to improve the political representation of women in politics in Indonesia. Based on the results of critical reflection researcher of secondary data, this research produced; The first: In Simultaneous Regional Elections in December 2015 there are 57 women out of 823 people who run for local office and 66 women out of 823 people who run for deputy regional head. Against this background categorized in incumbent, kinship network, party cadres, former member of Parliament/Council/Parliament, popular figures, entrepreneurs/businessmen, members of NGOs/CBOs, former members of the military/police/civil servants, as well as the former head of the region. Second: in improving the representation of women in the elections, there should be a formal education and advocacy on culturally in order to cleanse society of patriarkism and religious conservatism, so that voters can view the importance of the gender equality agenda in the election.